Infrared features of classic choroidal neovascularisation in exudative age-related macular degeneration. Issue 2 (4th November 2008) - Semoun, O; Guigui, B; Tick, S; Coscas, G; Soubrane, G; Souied, E H
Abstract : Aim: Wet age-related macular degeneration (AMD) represents a heterogeneous group of phenotypes, all defined by fluorescein angiography features (FA). Imaging of wet AMD is extensively described in literature, including colour pictures, FA, indocyanine green angiography (ICG) and optical coherence tomography (OCT). The purpose of this study was to describe features of infrared (IR) pictures of a homogeneous subgroup of classic choroidal neovascularisation (CNV) associated with wet AMD, Methods: We analysed 22 eyes of 22 consecutive patients with classic CNV. All patients underwent a complete ophthalmological examination including colour fundus photography, infrared picture, fluorescein angiography, indocyanine green angiography and an optical coherence tomography. Results: Infrared pictures revealed a whitish ring surrounding the neovascular lesion in all eyes (22/22). The whitish ring corresponded in all cases to the borders of the CNV defined on the early phase of FA and ICG pictures. The ring had an "O-shape" in 15/22 cases (68%) and a "U-shape" in 7/22 cases (32%). Conclusion: Analysis of infrared pictures in classic CNV constantly revealed a whitish ring that is correlated to the limits of the lesion. IR picture is a non invasive imaging of the macula, but the specificity of the features needs to be investigated in further studies.